Mitogen‐inducible gene‐6 partly mediates the inhibitory effects of prenatal dexamethasone exposure on endochondral ossification in long bones of fetal rats. (2nd June 2016) - Zhang, Xianrong; Shang‐Guan, Yangfan; Ma, Jing; Hu, Hang; Wang, Linlong; Magdalou, Jacques; Chen, Liaobin; Wang, Hui
Abstract: Background and Purpose: Prenatal exposure to dexamethasone slows down fetal linear growth and bone mineralization but the regulatory mechanism remains unknown. Here we assessed how dexamethasone regulates bone development in the fetus. Experimental Approach: Dexamethasone (1 mg·kg −1 ·day −1 ) was injected subcutaneously every morning in pregnant rats from gestational day (GD)9 to GD20. Fetal femurs and tibias were harvested at GD20 for histological and gene expression analysis. Femurs of 12‐week‐old female offspring were harvested for microCT (μCT) measurement. Primary chondrocytes were treated with dexamethasone (10, 50, 250 and 1000 nM). Key Results: Prenatal dexamethasone exposure resulted in accumulation of hypertrophic chondrocytes and delayed formation of the primary ossification centre in fetal long bone. The retardation was accompanied by reduced maturation of hypertrophic chondrocytes, decreased osteoclast number and down‐regulated expression of osteocalcin and bone sialoprotein in long bone. In addition, the mitogen‐inducible gene‐6 (Mig6) and osteoprotegerin (OPG) expression were stimulated, and the receptor activator of NF‐κB ligand (RANKL) expression was repressed. Moreover, dexamethasone activated OPG and repressed RANKL expression in both primary chondrocytes and primary osteoblasts, and the knockdown of Mig6 abolished the effect of dexamethasone on OPG expression. Further, μCT measurement showed loss of bone mass in femur of 12‐week‐old offspring with prenatal dexamethasone exposure. Conclusions and Implications: Prenatal dexamethasone exposure delays endochondral ossification by suppressing chondrocyte maturation and osteoclast differentiation, which may be partly mediated by Mig6 activation in bone. Bone development retardation in the fetus may be associated with reduced bone mass in later life.